A review of radio and podcasts in the USA and Malaysia - Anderson Ambah; Intan Soliha Ibrahim (UniSE Press, 2025)
The digital transformation of media has led to the rapid growth of podcasts as a complementary audio platform to conventional radio broadcasting. This paper presents a comparative review of podcast integration strategies and challenges among radio stations in the United States of America and Malaysia. Through a qualitative document analysis and systematic literature review from 2019 to 2024. The study examines how radio stations utilize podcasts for content delivery, audience engagement, and monetization. The United States of America will be a great benchmark for emerging podcast markets like Malaysia due to the United States’s position as a global leader in broadcasting industry while also providing a broad perspective on podcast broadcasting. This comparison can help researchers understand the difference between podcast in Malaysia and the United States of America in many significant ways. Findings reveal significant differences between both countries in podcast adoption stages, host selection, content strategy, marketing techniques, and technology infrastructure. While the United States of America exhibits mature practices with diversified business models and ad- vanned marketing, Malaysia remains in an early adoption phase with a focus on rebroadcasting. This review highlights the potential for podcasting as an innovation in the radio industry and offers insights for broadcasters aiming to bridge strategic gaps.